Effect of pH on sporicidal and microbicidal activity of buffered mixtures of alcohol and sodium hypochlorite. Issue 2 (February 1979) - Death, J E; Coates, D
Abstract : The effect of pH on the activity of buffered sodium hypochlorite solution, and a buffered methanol/sodium hypochlorite mixture, against Bacillus subtilis spores was investigated. The best results, considering both sporicidal activity and stability, were achieved in the pH range 7.6–8.1. The sporicidal activity and stability of five alcohol/hypochlorite mixtures, each containing a different alcohol and buffered to pH 7.6 and of hypochlorite alone buffered to pH 7.6, were compared. The mixtures were marginally more sporicidal than hypochlorite alone when fresh but were much less stable. An unbuffered methanol/hypochlorite mixture, a methanol/hypochlorite mixture buffered to pH 7.6, and hypochlorite alond buffered to pH 7.6 were all found to be effective against six vegetative organisms and spores of B. subtilis and Clostridium sporogenes. By buffering alcohol/hypochlorite mixtures or hypochlorite solution alone in the pH range 7.6–8.1, high sporicidal activity can be achieved with low concentrations of alcohol and hypochlorite. Such formulations show promise for the disinfection of heat-sensitive medical equipment.